(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article explores various linguistic approaches aimed at enriching vocabulary in English language learning. Vocabulary acquisition is a crucial component of language proficiency, yet learners often struggle with limited lexical resources. By analyzing linguistic theories, teaching methodologies, and applied practices, the article examines how vocabulary can be effectively developed. The study highlights morphology, semantics, pragmatics, and cognitive approaches as the most influential frameworks in enhancing lexical competence. Practical strategies, such as word-formation techniques, semantic mapping, collocation teaching, and contextualized learning, are considered as essential tools. The findings suggest that a combination of theoretical insights and learner-centered pedagogical strategies ensures sustainable vocabulary enrichment.